2007
DOI: 10.1529/biophysj.106.102749
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Lysozyme to Phospholipid Bilayers: Evidence for Protein Aggregation upon Membrane Association

Abstract: Biological functions of lysozyme, including its antimicrobial, antitumor, and immune-modulatory activities have been suggested to be largely determined by the lipid binding properties of this protein. To gain further insight into these interactions on a molecular level the association of lysozyme to liposomes composed of either 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine or its mixtures with 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-rac-glycerol, 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-rac-phosphatidyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 63 publications
7
106
0
Order By: Relevance
“…Kurts and colleagues (34) demonstrated that the mannose receptor delivered soluble Ova to an endosomal compartment equipped for cross-presentation; in contrast, macropinocytosis of Ova allowed for MHC class II presentation but not cross-presentation. HEL is not glycosylated and is presumably taken up by macropinocytosis when offered in soluble form; HEL can bind to constituents of plasma membranes, such as phospholipids (35) and glycosaminoglycans (36), but receptor-mediated uptake has not been shown. Our data indicate that soluble HEL rapidly enters late endosomes and does not remain in early endosomes for enough time to allow processing and cross-presentation; this feature of soluble HEL trafficking also hindered MHC class II presentation of type B epitopes, which are generated exclusively in early endosomes lacking the accessory molecule DM (37).…”
Section: Discussionmentioning
confidence: 99%
“…Kurts and colleagues (34) demonstrated that the mannose receptor delivered soluble Ova to an endosomal compartment equipped for cross-presentation; in contrast, macropinocytosis of Ova allowed for MHC class II presentation but not cross-presentation. HEL is not glycosylated and is presumably taken up by macropinocytosis when offered in soluble form; HEL can bind to constituents of plasma membranes, such as phospholipids (35) and glycosaminoglycans (36), but receptor-mediated uptake has not been shown. Our data indicate that soluble HEL rapidly enters late endosomes and does not remain in early endosomes for enough time to allow processing and cross-presentation; this feature of soluble HEL trafficking also hindered MHC class II presentation of type B epitopes, which are generated exclusively in early endosomes lacking the accessory molecule DM (37).…”
Section: Discussionmentioning
confidence: 99%
“…17 Immediately after its interaction within the lipid bilayer, lysozyme undergoes conformational changes with subsequent reorganization (oligomerization) that leads to vesicle clustering and amyloid fibril formation. [42][43][44][45] The concomitant presence of these effects contributes to a decrement of the lipid membrane fluidity (1/P).…”
mentioning
confidence: 99%
“…5). In this sense, VP11 differs from other basic proteins, such as lysozyme, which cause rapid aggregation with lipid vesicles (60,61,62). Rather, it functions as a trigger for the binding of the large major capsid protein VP17, which in turn results in a rapid aggregation of the protein-membrane complex.…”
Section: Discussionmentioning
confidence: 99%